Oxidative Dissolution of Arsenopyrite by Mesophilic and Moderately Thermophilic Acidophiles - Tuovinen, Olli H. (1994)
The purpose of this work was to determine solution- and solid-phase changes associated with the oxidative leaching of arsenopyrite (FeAsS) by Thiobacillus ferrooxidans and a moderately thermoacidophilic mixed culture. Jarosite [KFe(3)(SO(4))(2)(OH)(6)], elemental sulfur (S(0)), and amorphous ferric arsenate were detected by X-ray diffraction as solid-phase products. The oxidation was not a strongly acid-producing reaction and was accompanied by a relatively low redox level. The X-ray diffraction lines of jarosite increased considerably when ferrous sulfate was used as an additional substrate for T. ferroxidans. A moderately thermoacidophilic mixed culture oxidized arsenopyrite faster at 45°C than did T. ferroxidans at 22°C, and the oxidation was accompanied by a nearly stoichiometric release of Fe and As. The redox potential was initially low but subsequently increased during arsenopyrite oxidation by the thermoacidophiles. Jarosite, S(0), and amorphous ferric arsenate were also formed under these conditions.